Answer:
Step-by-step explanation:
In order to know which equation we need to consider, we have to check the value of x. If x is negative, we will replace x in the first equation and if x is positive or null we will replace it in the second equation.
(a) x=-4 so x is negative. We use the first equation [tex]f(x)=5x+7[/tex] and we have [tex]f(-4)=5*(-4)+7=-13[/tex]
(b)x=2 and is positive so we use the second equation [tex]f(x)=7x+8[/tex]. The result is [tex]f(2)=7*(2)+8=22[/tex]
(c)x=0 In this case the function is defined by the second equation [tex]f(x)=7x+8[/tex]. So [tex]f(0)=7*(0)+8=8[/tex]
(d)Here we have both case in the same calcul. We need to calculate the fonction values of each one and then make the sum.
With [tex]f(-100)[/tex], x=-100 and is negative so we use the first equation [tex]f(x)=5x+7[/tex] and we have [tex]f(-100)=5*(-100)+7=-493[/tex].
With [tex]f(00)[/tex], x=100 ans is positive so we use the second equation [tex]f(x)=7x+8[/tex] and get [tex]f(100)=7*100+8=708[/tex].
We add them to get the result : [tex]f(-100)+f(100)=-493+708=215[/tex]
(e)[tex]f(-4)=-13[/tex]
(f)[tex]f2)=22[/tex]
(g)[tex]f(0)=8[/tex]
(h)[tex]f(-100)+f(100)=215[/tex]